2007
DOI: 10.2741/2378
|View full text |Cite
|
Sign up to set email alerts
|

p53 in breast cancer: mutation and countermeasures

Abstract: p53 is the primary arbiter of the mammalian cell's response to stress, the governor of life and death. It is the nexus upon which signals converge from an array of sensors that detect damage to DNA or to the mitotic spindle or the cytoskeleton, hypoxia, cell detachment, growth factor deprivation, oncogene expression and other forms of stress. Depending on the type, intensity and duration of the signals, p53 in turn transactivates batteries of genes specifying cell cycle arrest, DNA repair, apoptosis, or other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 106 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…These results indicated that theaflavins induce apoptosis in p53-dependent manner, although in cells naturally devoid of p53 or expressing non-functional p53 a minimal p53-independent apoptosis was noticed indicating the existence of some parallel apoptotic pathways in these cells. Since at least one third of breast cancers bear mutations in p53 and to date 1400 p53 mutations have been detected in mammary epithelial carcinoma [19], it is possible that as tumors progress, the functional p53 gene is mutated and the loss of p53 function leads to the activation of alternative cell death pathways independent of p53, as was apparent in response to theaflavins. Subsequently a search for the role of transcriptional activity of p53 in theaflavin-induced apoptosis revealed that Bax, a known transcriptional target of p53 [2], was also up-regulated on theaflavin treatment.…”
Section: Discussionmentioning
confidence: 97%
“…These results indicated that theaflavins induce apoptosis in p53-dependent manner, although in cells naturally devoid of p53 or expressing non-functional p53 a minimal p53-independent apoptosis was noticed indicating the existence of some parallel apoptotic pathways in these cells. Since at least one third of breast cancers bear mutations in p53 and to date 1400 p53 mutations have been detected in mammary epithelial carcinoma [19], it is possible that as tumors progress, the functional p53 gene is mutated and the loss of p53 function leads to the activation of alternative cell death pathways independent of p53, as was apparent in response to theaflavins. Subsequently a search for the role of transcriptional activity of p53 in theaflavin-induced apoptosis revealed that Bax, a known transcriptional target of p53 [2], was also up-regulated on theaflavin treatment.…”
Section: Discussionmentioning
confidence: 97%
“…C-erB-2 is one of the common oncogene for breast cancer (McCann et al 1989;Lopez-Guerrero et al 2003); the positive expression was mainly found in poorly differentiated and invasive breast cancer. P53 is the inhibiting gene of tumorigenesis; the expression of mutant p53 could cause cell transformation and cancer (Royds and Iacopetta 2006;Kumar et al 2007;Khoury and Bourdon 2011). Last but not least, PCNA could indicate the proliferation activity of tumor cells (Kato et al 2002;Malkas et al 2006), and is important in prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…The model also suggests that cells being shed by the primary tumour are fully metastatic and that cells that have metastasized to a secondary site should also be able to leave that site to set up at a tertiary site (Klein 1998;Klein 2009). Mutations in genes such as BRCA1, BRCA2, p53 and RB and amplification of the HER-2 receptor at the site of the primary tumour have been identified as being predictive of poorer outcome for breast cancer patients, consistent with this model (Slamon, Clark et al 1987;Ross and Fletcher 1999;Bordeleau, Lipa et al 2007;Bosco and Knudsen 2007;Kumar, Walia et al 2007;Baker, Quinlan et al 2010). The parallel progression model suggests that tumour cells may disseminate from the site of the primary tumour very early in its development and may be subsequently genetically modified in the metastatic niche where they later settle (Klein 2009).…”
Section: Metastasismentioning
confidence: 49%